Homing Guidance Using Spatially Quantized Signals - R. A. G. Bencatel (2017)
This paper considers homing guidance for a vehicle with a single omnidirectional receiver traveling to a stationary, omnidirectional transmitting beacon by using spatially quantized signal strength measurements. Two homing strategies are presented, and simulations are performed for cases with signal noise and vehicle turn rate limits. The first strategy is the Oyler strategy, which adapts a sliding mode controller and observer from the previous work. The second strategy is based on constant heading changes (CHCs) each time a range increment is detected, and this strategy is shown to be sufficient for homing. This study also discusses a signal filter designed to improve the homing controllers' performance. Performance metrics are developed for strategy evaluation and parameter optimization. The performance of each guidance strategy is shown through simulations for a variety of conditions. The Oyler strategy guides the vehicle to the beacon more efficiently than the constant heading change strategy, but it comes with a slight penalty in success rate.